Alfa-tocoferol previne os déficits cognitivos, motores e neuronais em um modelo de parkinson progressivo em ratos - Silva, Aldair José Sarmento (2014)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder that affects 1-2% of world population, with a higher prevalence among men. The main symptoms are of motor nature, and include bradikynesia, rigidity, postural instability and tremor. In addition, non-motor symptoms may occur, such as sleep disturbances, anxiety, depression, and cognitive deficits. The motor alterations are a consequence of the irreversible loss of dopaminergic neurons mainly in the substantia nigra pars compacta. The most effective current treatment for PD is L-DOPA administration. However, this drug, despite amegliorating symptoms, does not interfere with the neurodegeneration, and thus has limitations at long term. Thus, alternative treaments that could act by neuroprotective mechanisms have been considered, such as antioxidant agents. The mechanisms related to the symptoms and progressive nature of PD can be studied in animal models. In this sense, the aim of the present study was to investigate the effects of the antioxidant α-tocopherol on the motor, cognitive and neuronal deficits induced by repeated treatment with reserpine (a progressive pharmacological model of parkinsonism). Rats submitted to the reserpine protocol were concomitantly treated with α-tocopherol. The results showed that the repeated treatment with reserpine, as expected, induced progressive motor and cognitive decrements, as well as dimished tyrosine hydroxylase immunostaining in the substantia nigra pars compacta and striatum. These deficits were not present in the animals that were co-treated with α-tocoferol, suggesting a possible neuroprotective effect induced by this antioxidant agent. In conclusion, α-tocoferol was able to prevent the alterations caused by repeated reserpine administration. In addition, our study suggest that low-dose reserpine-induced progressive motor and cognitive deficits can be useful in the study of possible neuroprotective strategies for PD.